A Critical Assesment of Marketing Strategies that Attract Visitors to Heritages Destination of Indonesia - Ananta Budhi Danurdara; Digma Khariza Rifanggi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research aims to review from previous literature about heritage marketing, to analyze an effective marketing strategies that attract visitors to visit heritage sites in Indonesia, and offers recommendations of marketing strategies to less popular heritage destinations in Indonesia. This study uses a quantitative approach.  This research has a pretty wide range of target population, on the very least are people aged above 16 who ever travel or aware of tourism activity. The Google Forms questionnaire was distributed via media social network and direct e-mail on 4th March 2021. After the research is conducted, the collected raw data need to be process by mean to make it understandable which include converting it to an easier to understand forms such as pie chart, table, etc. To do that, SPSS and Microsoft Excel are used to process the raw data. We find that the awareness on Indonesia heritage tourism is still in moderate level, leaving plenty of room for promotion activities to increase awareness. Pull factors such as the attractiveness of the destination, on-going event within the tourism location, and the culture present in the destination are the major considerations in tourist travel decision to visit heritage site. Promoting the heritage site’s authenticity is considered an effective marketing strategy as it will be an addition of pull factor to influence tourist visit. UNESCO’s World Heritage Site title is approved to be used as a value-added branding for heritage destination. There are certain perceptions that Indonesia heritage tourism attractions are currently branded or associated which in descending order are: tropical setting, flora & fauna, foods, and low cost. Further maximizing these affiliated perceptions will potentially increase the market position of Indonesia heritage tourism.